Legal framework and problems of interaction of executive authorities in the sphere of tax security: International comparative analysis - KUBATOV, Ilimbek; MAMASAIDOV, Alimardonbek; OITEMIROV, Makhmud; AMANALIEV, Urmat; KURAMAEVA, Nargiza (Revista Jurídica Portucalense, 2025)
The purpose of the study is to examine the legal framework and issues of coordination of executive bodies in the field of tax security using an international comparative approach. As part of the research methodology, both national and international legal acts, as well as statistical data related to tax revenues, the level of shadow economy and the effectiveness of tax administration were analysed. Special attention was paid to the international programme aimed at combating tax evasion. The study considers legislative acts of the Kyrgyz Republic regulating tax relations, such as the Constitution of the Republic of Kyrgyzstan and the Tax Code of the Republic of Kyrgyzstan. In addition, the international experience of such countries as Estonia, the Netherlands, Singapore, Sweden, Germany and Canada, which have achieved a high level of efficiency of tax administration due to the introduction of digital technologies, transparency, and development of interagency cooperation, was considered. The study found that a high degree of coordination between tax, financial and customs authorities significantly improves tax security and reduces the risks of tax evasion. The study found that countries with a high degree of digitalization of tax administration, such as Estonia, managed to reduce the level of shadow economy to 10-15% of gross domestic product, which is significantly lower than in states with less efficient tax systems, such as Kyrgyzstan. The findings point to the need to improve the legal framework and introduce digital tools in the area of tax security to improve the efficiency of interaction between government agencies and reduce the shadow economy.